Comparative effectiveness of different stimulation methods on yield performance of Hevea brasiliensis - Rajagopal R; Thomas K U; Vijayakumar K R (Placrosym XIV, 2000, Hyderabad, India : Programme and Abstracts.p68)
Hevea brasiliensis Muell. Arg is the main source of natural rubber. Various methods are adopted for the application of the yield stimulant ethephon. In this paper the efficacy of different methods of stimulation, such as lace, groove, panel and bark with ethephon at different concentrations viz 0;. 2.5;, 5;and 10;were evaluated in clone RRII 118 under 1/25 d/6 frequency of tapping. The unstimulated trees under 1/2S d/2 frequency of tapping served as the control. The results clearly indicated that rubber yield (g/tree/tap) was significantly affected by the stimulation treatments. Among the various treatments, panel application at 2.5;level gave comparable or more yield than all other treatments. In another trial using clone RRII 105 under 1/2S d/3 frequency of tapping, panel application with 2.5;ethephon gave comparable yield stimulation to bark application with 5;. Results of the study show that the yield stimulation in rubber is more effective under panel application. There was also no panel injury noticed during the study period of six years. The method is labour saving and requirement of ethephon can be reduced by 50 percent, leading to reduction in cost of production in cost of production of natural rubber and in increasing the efficiency of crop production.
Keywords: Ethephon; Hevea brasiliensis; Yield